Implementasi Algoritme Speck Untuk Enkripsi One-Time Password Pada Two-Factor Authentication - Moh. Ahsani Taqwim; Ari Kusyanti; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Static authentication is very vulnerable to attacks, Therefore, two-factor authentication is carried out by adding OTP as a factor in the authentication. However, even with all the conveniences offered by OTP, OTP is still very vulnerable to attacks, there are many attacks on OTP such as sniffling, wireless interception, etc. Therefore, it is necessary to have a second security for OTP. The SPECK algorithm provides excellent performance in both software and hardware, SPECK Family also has a variety of block and key sizes to match the application requirements and security needs without hindering the performance. OTP is encrypted with the SPECK algorithm to prevent attacks that directed at OTP. The OTP is encrypted with a key and sent to the user which is then sent back by the user to the system to be decrypted using the user's key. The validated OTP is then deleted to avoid duplicate OTPs. The testing of sniffing and KPA attack that was done to OTP was successfully prevented using SPECK algorithm. We can conclude that the result is invisible in sniffing attack testing, and the plaintext generated from KPA didn't match the main plaintext. The validation of the SPECK data is also true because it matches the test vector.